PENINGKATAN KEMAMPUAN GURU DALAM MENYUSUN SOAL HOTS MELALUI MUSYAWARAH GURU MATA PELAJARAN DI SMPN 1 RAMBAH - Yelleson Syuryadi (STKIP ROKANIA, 2019)
The purpose of this research is to find out and describe the ability of teachers in compiling HOTS questions through Subject Teacher Consultation. This study is classified as a principal's action research involving 18 subject teachers based on the criteria of HOTS question formulation. The study was conducted in 2 (two) cycles. Questions that have been completed are analyzed and assessed based on 3 parameters that have been established in a way that is. 1), aspects of the suitability of the Problem with learning objectives, 2) behavioral aspects of the level of difficulty of Taxom Blom (C1-C6), and to. 3), the use of Indonesian is good and right. Meanwhile, to find out the activities of the teacher at work, the researcher completes the measuring instrument with observation guidelines. The aspects observed in this activity consisted of 5 aspects of teacher activities, namely: a), material aspects, b), activeness aspects, c), internal presentation aspects, d), external presentation aspects and e), expert panel aspects. Based on the criteria mentioned above, from the first cycle and second cycle the average score showed an increase, from an average score of 69.6 to a score of 86.13 with an increase of 16.53%. This means that the teacher's effort in compiling HOTS questions has met the specified criteria. Thus it can be concluded that through the Subject Teachers' Consultation in the preparation of HOTS questions, it has succeeded in making HOTS questions based on the criteria set.